Swarm-dular quadcopter: bringing swarm robotics and modular robotics together - Mohan, Deepak; R. Guruprasad, K (International Journal of Engineering and Technology, 2018)
In this paper, we present a new concept in robotics, which we call as swarm-dular robotics, by bringing together swarm robotics and modular robotics. We propose a swarm-dular quadcopter, which is aÂ modularÂ quadcopter, where, multiple wheeledÂ ground robots (AGVs), whichÂ are part of a heterogenous swarm orÂ multi-robotic(agent) system (MRS or MAS), attach/dock Â together to form an aerial quadcopter robot. We provide a conceptual design and demonstrate the proposed system using simulation experiments in Â Robot Operating System (ROS). Behavior of the system as both a swarm and a modular quadcopter UAV are demonstrated.